Examining Teacher and Student Talk Ratio in English Speaking Classess of Second-Grade Students at SMAN 2 Jeneponto - ANGGI OKTAVIA NUR HS; Haryanto Atmowardoyo; Geminasti Sakkir (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This research aimed to investigate the distribution of teacher and student talk in English speaking classes for second grade students at SMAN 2 Jeneponto. The Flanders interaction analysis category system (FIACS) served as the primary observation instrument to analyze classroom interaction, categorizing instances of teachers talk, students talk, and silence. This study uses a quantitative approach, including a case study design with 1 English teacher and, 30 students as participants. Data were collected through a classroom observation, tally sheet, and video recordings then analyzed using FIACS based techniques to quantify teacher and student contributions. The findings revealed the proportion of teacher talk in student, talk during class activities, where teacher and student talk are relatively balanced. With the teacher speaking for 50.22% of the time, and students for 43.17%. This distribution suggests an engaging classroom environment, where students are encouraged to contribute almost as much as the teacher, while the remaining 6.6% prefer to silence, Not only that, based on the FIACS 10 types of classroom interaction were discovered there are accept feeling, praise and encouragement, accepts or uses ideas of students, asking questions, lecturing, giving direction, criticizing or justifying authority, student talk response, student talk initiation, and silence. Meanwhile, there are 4 characteristics of classroom interaction. They are teacher support, content cross, teacher control and students participationKeywords: Classroom interaction,FIACS (Flanders Interaction Analysis System, Teacher-students talk ratio